Angularly resolved characterization of ion beams from laser-ultrathin foil interactions. (30th September 2016) - Scullion, C.; Doria, D.; Romagnani, L.; Ahmed, H.; Alejo, A.; Ettlinger, O.C.; Gray, R.J.; Green, J.; Hicks, G.S.; Jung, D.; Naughton, K.; Padda, H.; et al.
Abstract: Methods and techniques used to capture and analyze beam profiles produced from the interaction of intense, ultrashort laser pulses and ultrathin foil targets using stacks of Radiochromic Film (RCF) and Columbia Resin #39 (CR-39) are presented. The identification of structure in the beam is particularly important in this regime, as it may be indicative of the dominance of specific acceleration mechanisms. Additionally, RCF can be used to deconvolve proton spectra with coarse energy resolution while mantaining angular information across the whole beam.